A morphospace for synthetic organs and organoids: the possible and the actual. - Ollé-Vila, Aina; Durán-Nebreda, Salva; Conde-Pueyo, Núria; Montañez, Raúl; Solé, Ricard V. (Oxford University Press, 2016)
Efforts in evolutionary developmental biology have shed light on how organs are developed and why evolution has selected some structures instead of others. These advances in the understanding of organogenesis along with the most recent techniques of organotypic cultures, tissue bioprinting and synthetic biology provide the tools to hack the physical and genetic constraints in organ development, thus opening new avenues for research in the form of completely designed or merely altered settings. Here we propose a unifying framework that connects the concept of morphospace (i.e. the space of possible structures) with synthetic biology and tissue engineering. We aim for a synthesis that incorporates our understanding of both evolutionary and architectural constraints and can be used as a guide for exploring alternative design principles to build artificial organs and organoids. We present a three-dimensional morphospace incorporating three key features associated to organ and organoid complexity. The axes of this space include the degree of complexity introduced by developmental mechanisms required to build the structure, its potential to store and react to information and the underlying physical state. We suggest that a large fraction of this space is empty, and that the void might offer clues for alternative ways of designing and even inventing new organs.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/18017?template=romeo
Keywords: Biología sintética; Ingeniería de tejidos; Synthetic Biology; Organoids; Development; Morphospace; Cell engineering; Tussie engineering